Pendidikan dan Pelatihan Bantuan Hidup Dasar pada Komunitas Lifeguard di Lokasi Wisata Pantai Cermin - Muhammad Jalaluddin Assuyuthi Chalil; Irfan Hamdani (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
Pantai Cermin Kanan Village is one of the villages in Pantai Cermin Subdistrict, Serdang Bedagai Regency, North Sumatra Province, located on the east coast of Sumatra Island. Because of this location, the Pantai Cermin Kanan Village has long been recognized by the community as a beautiful beach tourism destination and is visited every weekend and other holidays. The local government has sought to advance the coastal tourism industry in this village by building good access to tourist sites, and equally important is establishing the Pantai Cermin Puskesmas as the Regional Technical Implementation Unit (UPTD) of the Tourism Health Center. Based on these data, training is needed that aims to increase the knowledge and ability to conduct Basic Life Assistance (BHD) for the "Lifeguard" community of coastal tourist sites in Pantai Cermin Kanan Village and health workers in the work area of Cermin Beach Tourism Puskesmas as an effort to improve rescue management services first cases of cardiac arrest in drowning victims and emergency cases of cardio respiration. This activity was carried out for 2 days and was attended by 40 participants, consisting of 2 stages, namely the theory and technical practice of BHD on manikin. The results of this activity were an increase in knowledge and ability to do BHD between before and after training (p = 0.00) in the health workforce group. So it was concluded that this activity could help increase knowledge and implementation of BHD and still needed to be continued, especially in the "Lifeguard" community.